Work in the post-COVID-19 pandemic: the case of South Korea. Issue 3 (3rd April 2022) - Shin, Kwang-Yeong
ABSTRACT: This paper addresses the transformation of work and employment in the period of post-COVID-19 in South Korea. The COVD-19 pandemic displays the failure of the market in managing the public health crisis and the crisis of neoliberal globalization, demanding massive state intervention to reproduce the stability of the social system. COVID-19 disrupted global production networks and global supply chains, generating economic disorder and mass unemployment. It also revealed the segmented labour market based on firm size, gender, employment status, and inadequate social protection. The COVID-19 pandemic, therefore, reveals problems that are embedded in the Korean economy, though at the same time provides an opportunity to discuss alternatives to the neoliberal economy. In particular, discourses on universal basic income and universal unemployment insurance have gained popularity as COVID-19 has disrupted mass' livelihood through promoting precarious work and expanding the population unprotected by labour laws and the social security system.